Answer:
90
Step-by-step explanation:
The simplified version of the expression is this: 5(x² + 9) ÷ x.
Answer:
-8
Step-by-step explanation:
m= y₂- y₁/ x₂-x₁
m= 1-9/7-6
m= -8/1
m= -8
Its a squared + xb squared = c squared so its 11 squared + 11 squared equals c squared. So I'm gonna take it down to the next step and say 11x11+ 11x11= c squared, then you end up with 121+121= c squared then you add those two and end up with 242= c squared, so then you find the square root of 242 so you should end up with 15.5 and the number goes on and on and on
Answer:
4
Step-by-step explanation:
-8+12=4
4-12=-8